2022
DOI: 10.3390/molecules27082574
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitory and Antimicrobial Benzoylphloroglucinols from Garcinia schomburgakiana Fruits: In Vitro and In Silico Studies

Abstract: α-Glucosidase plays a role in hydrolyzing complex carbohydrates into glucose, which is easily absorbed, causing postprandial hyperglycemia. Inhibition of α-glucosidase is therefore an ideal approach to preventing this condition. A novel polyprenylated benzoylphloroglucinol, which we named schomburgkianone I (1), was isolated from the fruit of Garcinia schomburgkiana, along with an already-reported compound, guttiferone K (2). The structures of the two compounds were determined using NMR and HRESIMS analysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…The duplication of all these data in association with the mass data confirmed that 2/3 was a mixture of two polyisoprenylated benzophenone derivatives. The 13 C NMR spectrum of 2/3 displayed characteristic signals for a bicyclo[3.3.1]nonane ring as pairs of carbons at ẟ C 170.3/170.5 (C-1), 125.6/125.9 (C-2), 193.3/193.6 (C-3), 68.9/69.0 (C-4), 48.3/48.4 (C-5), 2×39.4 (C-6), 38.1/38.3 (C-7), 51.2/51.5 (C-8), and 206.2/206.3 (C-9) [ 37 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duplication of all these data in association with the mass data confirmed that 2/3 was a mixture of two polyisoprenylated benzophenone derivatives. The 13 C NMR spectrum of 2/3 displayed characteristic signals for a bicyclo[3.3.1]nonane ring as pairs of carbons at ẟ C 170.3/170.5 (C-1), 125.6/125.9 (C-2), 193.3/193.6 (C-3), 68.9/69.0 (C-4), 48.3/48.4 (C-5), 2×39.4 (C-6), 38.1/38.3 (C-7), 51.2/51.5 (C-8), and 206.2/206.3 (C-9) [ 37 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the combination of the DEPT 135 and HSQC confirmed the presence of seven isopent-2-enyl units, one isopent-3-enyl with the characteristic signals at δ C /δ H [22.4/1.94 (C-39/H-39), 35.4/1.21 (C-40/H-40), 145.0 (C-41), 21.5/1.74 (C-42/H-42), and 110.4/4.79 (C-43/H-43)], and one dimethylpyrane moiety identified by the signals at δ C /δ H {[28.3/0.89 (C-29/H-29), 41.8/1.10 (C-30/H-30), 86.2 (C-31), 27.9/0.89 (C-32/H-32), 20.6/1.27 (C-33/H-33), 2 ], [28.3/0.94 (C-29/H-29), 42.9/1.10 (C-30/H-30, 86.5 (C-31), 28.0/0.89 (C-32/H-32), 20.7/1.29 (C-33/H-33), 3 ]}. All these data indicated that the structures of 2/3 are closely related to shomburgkianone I [ 39 ]. The location of the dimethylpyrane moiety on the bicyclo unit was deduced by the HMBC correlation of H-29 (ẟ H 3.00/3.05)/C-8 (ẟ C 51.2/51.5), C-1 (δ C 170.3/170.5), C-30 (δ C 41.8/42.9), and C-31 (δ C 86.5).…”
Section: Resultsmentioning
confidence: 99%
“…The validation of the model was based on the values of RMSD bet ranked pose and reference pose, one small ligand that is available in the target enzyme, . 39,40…”
Section: Methodsmentioning
confidence: 99%
“…The validation of the model was based on the values of RMSD bet ranked pose and reference pose, one small ligand that is available in the target enzyme, 4WCU. 39,40 3.6. Molecular dynamics simulation A top-docked pose with high binding energy was used in an MD simulation employing the GROMACS soware program 41 with the GROMOS9643a1 force eld to ensure conformational stability.…”
Section: In Silico Molecular Docking Modelmentioning
confidence: 99%
“…To date, there have been two reports on the phytochemical constituents of G. schomburgkiana fruits, uncovering 14 phloroglucinols and xanthones. 8,10 In 2016, Le and co-workers reported the presence of 12 new phloroglucinols, showing strong cytotoxicity against several cancer cell lines. 8 In 2021, Nguyen and co-workers reported two potent alpha-glucosidase inhibitors, namely schomburgkianone I and guttiferone K, isolated from Thai fruits.…”
Section: Introductionmentioning
confidence: 99%